Micrococcal nuclease cleavage of nucleotide linked to glutamine synthetase yields phosphotyrosine at the ligation site. - Martensen, T M (1982)
The activity of micrococcal nuclease was studied on a novel substrate, denatured adenylylated glutamine synthetase [L-glutamate: ammonia ligase (ADP-forming), EC 6.3.1.2], which contains a unique tyrosyl residue linked through a phosphodiester bond to 5'-AMP. The products of the digestion were adenosine and O-phosphotyrosylglutamine synthetase. The Km of the macromolecular substrate with the nuclease was 1/40 that of the synthetic substrate, nitrophenyl-pdT, which is commonly used for assay of the enzyme. Native adenylylated glutamine synthetase was not deadenosylated by micrococcal nuclease under the conditions that permit rapid deadenosylation of denatured glutamine synthetase. Failure to attack native glutamine synthetase is probably not due to steric factors because the native enzyme is deadenylylated by snake venom phosphodiesterase under identical conditions. The inability of micrococcal nuclease to deadenosylate native glutamine synthetase may be due to the formation of an inactive complex because the native protein inhibited the nuclease activity on the denatured protein.